1). Rozłóż na iloczyny:
a) ax- ay =
b) mn- n =
c) cd- bc =
d) ab + b =
e) x⁴ -x² =
f) mx -m =
g) -2a -5ab =
h) 7ab - 7bc =
i) -2mn - 4n =
j) mn - n² =


2). Rozłóż na czynniki wyłączając wspólny czynnik przed nawias:

a) 3x² - 6x² =
b) 9m⁴ + 6m³ =
c) 6z⁴ - 12z⁶ =
d) 15a³ +5a² =
e) 7y⁵ - 21y³ =

Pilne na jutro..!! ;]]
Daję naj..;******

3

Odpowiedzi

2010-03-04T17:47:30+01:00
Zad 1
a) ax- ay =a(x-y)
b) mn- n =n(m-1)
c) cd- bc =c(d-b)
d) ab + b =b(a+1)
e) x⁴ -x² =x^2(x^2-1)
f) mx -m =m(x-1)
g) -2a -5ab =-a(2+5b)
h) 7ab - 7bc =7b(a-c)
i) -2mn - 4n =-2n(m+2)
j) mn - n² = n(m-n)

Zad 2
a) 3x² - 6x² =3x^2(1-2)=-3x^2
b) 9m⁴ + 6m³ =3m^3(3m+2)
c) 6z⁴ - 12z⁶ =6z^4(1-2z^2)
d) 15a³ +5a² =5a^2(3a+1)
e) 7y⁵ - 21y³ = 7y^3(y^2-3)
4 4 4
Najlepsza Odpowiedź!
2010-03-04T17:51:01+01:00
1). Rozłóż na iloczyny:
a) ax- ay =a(x-y)
b) mn- n =n(m-1)
c) cd- bc =c(d-b)
d) ab + b =b(a+1)
e) x⁴ -x² = x²(x²-1)
f) mx -m =m(x-1)
g) -2a -5ab =-a(2+5b)
h) 7ab - 7bc =7b(a-c)
i) -2mn - 4n =-2n(m+2)
j) mn - n² =n(m-n)

2). Rozłóż na czynniki wyłączając wspólny czynnik przed nawias:

a) 3x² - 6x² = 3x²(1-2)
b) 9m⁴ + 6m³ = 3m³(3m+2)
c) 6z⁴ - 12z⁶ =6z⁴(1-2z²)
d) 15a³ +5a² =5a²(3a+1)
e) 7y⁵ - 21y³ =7y³(y²-3)
4 4 4
2010-03-04T17:54:44+01:00
A) ax- ay =a*a-x*y
b) mn- n =m*n-n
c) cd- bc =c*d-b*c
d) ab + b =a*b+b
e) x⁴ -x² =x*x*x*x-x*x
f) mx -m =m*x-m
g) -2a -5ab =-2*a-5*a*b
h) 7ab - 7bc =7*a*b-7*b*c
i) -2mn - 4n =-2*m*n-4*n
j) mn - n² = m*n-n*n


a) 3x² - 6x² =3x²(1-2)
b) 9m⁴ + 6m³ =3m³(3m+2)
c) 6z⁴ - 12z⁶ =6z⁴ (1-2z²)
d) 15a³ +5a² =5a²(3a+1)
e) 7y⁵ - 21y³ =7y³(y²-3)
2 3 2